Psoriasis Patients Suffer From Worse Periodontal Status—A Meta-Analysis - Qiao, Pengyan; Shi, Quan; Zhang, Rong; E, Lingling; Wang, Peihuan; Wang, Juncheng; Liu, Hongchen (Frontiers in Medicine, 2019)
Background and Objective: Patients with psoriasis have a significantly elevated risk of periodontitis compared with the nonpsoriasis controls. However, the data regarding the difference in the periodontal health status of the psoriasis patients and the nonpsoriasis controls are limited and inconsistent; hence, a specialized meta-analysis that quantitatively compared the periodontal status between the psoriasis and nonpsoriasis subjects by evaluating the related clinical periodontal indexes was needed. The aim of this meta-analysis was to quantitatively evaluate whether the periodontal status of psoriasis patients is worse than that of nonpsoriasis subjects. Methods: We searched PubMed and EMBASE for all eligible studies that compared the periodontal status between psoriasis patients and nonpsoriasis subjects. The studies were screened based on pre-established inclusion criteria. After extracting the available periodontal indexes from the included studies, the weighted mean difference (WMD) with 95% confidence intervals (CIs) was calculated by pooling the mean and standard deviations (SD) of each index. Results: In total, 8 studies, including 812 psoriasis patients and 772 nonpsoriasis subjects, were included in our meta-analysis, and the publication dates ranged from 2013 to 2019; eight periodontal indexes were analyzed. The WMD (95% CIs) for each index were: bleeding on probing (%), 9.188 (4.046–14.330, P < 0.001); probing depth (mm), 0.524 (0.183–0.865, P = 0.003); clinical attachment loss (mm), 0.408 (0.051–0.765, P = 0.025); plaque index, 0.186 (−0.170 to 0.543, P = 0.306); gingival index, 0.458 (−0.413 to 1.328, P = 0.303), remaining teeth, −1.709 (−2.106 to −1.312, P < 0.001); missing teeth, 1.130 (0.275–1.985, P = 0.010); the level of alveolar bone loss (mm), 0.400 (0.102–0.698, P = 0.008). Conclusion: In summary, our meta-analysis revealed that psoriasis patients suffer from worse periodontal health than do nonpsoriasis subjects, mainly characterized by worse gingival inflammation, more alveolar bone loss, fewer remaining teeth and more missing teeth. Considering the limitations of this meta-analysis, more high-quality and well-designed studies are needed to validate our conclusions in the future.